Hormone Therapy Reduces Recurrence in Stage II-IV Uterine Low-Grade Endometrial Stromal Sarcomas: A Retrospective Cohort Study - Huang, Xiaodi; Peng, Peng (Frontiers in Oncology, 2022)
Low-grade endometrial stromal sarcoma (LG-ESS) is a rare and indolent malignancy. Hormone therapy has been reported as an adjuvant treatment for LG-ESS, although its effectiveness is controversial. Here we aimed to investigate the effects of postoperative hormone therapy on recurrence in patients with uterine LG-ESS. Between January 2010 and December 2019, a total of 152 patients (23 with and 129 without fertility-sparing) with a diagnosis of primary uterine LG-ESS confirmed by pathologists were enrolled in this study. In the cohort without fertility-sparing, 22 (17.7%) patients had recurrence, and the median disease-free survival (DFS) was 47 (2-130) months; only one of these patients died of LG-ESS. No significant difference was found in recurrence between the groups with and without hormone therapy (p=0.802). However, subgroup analysis showed that hormone therapy decreased the recurrence rate in stage II-IV (p=0.001, HR 0.144, 95% CI: 0.038-0.548), but not in stage I disease (p=0.256). High-dose progestins notably reduced recurrence (p=0.012, HR 0.154, 95% CI: 0.036-0.660), whereas non-progestin therapy marginally influenced recurrence (p=0.054) compared with no hormone therapy in stage II-IV disease. Moreover, hormone therapy within 12 months was effective in reducing recurrence (p=0.038, HR 0.241, 95% CI: 0.063-0.922). Ovarian preservation (p=0.004, HR 6.250, 95% CI: 1.786-21.874) and negative expression of ER/PR (p=0.000, HR 23.249, 95% CI: 4.912-110.026) were high-risk factors for recurrence in patients without fertility-sparing. In the fertility-sparing cohort, 15 (65.2%) patients experienced recurrence, and the median DFS was 24 (3-107) months. Six patients successfully delivered healthy fetuses, and five received hormone therapy. Twelve patients finally accepted hysterectomy after repeated recurrence, and only two of them had given birth before surgery. Patients who received hormone therapy showed longer DFS, although this difference was not statistically significant (p=0.466). In conclusion, postoperative hormone therapy reduces recurrence in patients with stage II–IV uterine LG-ESS without fertility-sparing, and high-dose treatment with progestins within 12 months is recommended. Bilateral oophorectomy can also reduce the risk of recurrence. Patients with fertility-sparing have a high risk of recurrence and poor pregnancy outcomes, and hormone therapy is a reasonable choice in postoperative management.